2003
DOI: 10.1046/j.1469-8137.2003.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 and nitrogen availability have interactive effects on canopy carbon gain in rice

Abstract: Summary• Here we analysed the effects of CO 2 (C a ) elevation and nitrogen availability on canopy structure, leaf area index (LAI) and canopy photosynthesis of rice ( Oryza sativa ).• Rice was grown at ambient and elevated C a ( c. 200 µmol mol − 1 above ambient, using the free-air CO 2 enrichment, FACE) and at two N availabilities. We measured leaf area, area-based leaf N contents and leaf photosynthesis, and calculated net daily canopy photosynthesis.• FACE plants had higher light-saturated rates of photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…It has been shown that predicted LAI values are strongly correlated with measured LAIs (Anten et al 2000). Anten et al (2004) applied the concept of optimal LAI to stands of rice grown under free air CO 2 enrichment (FACE). In this experiment, LAI increased with increasing nitrogen availability but was not affected by elevated CO 2 .…”
Section: Canopymentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that predicted LAI values are strongly correlated with measured LAIs (Anten et al 2000). Anten et al (2004) applied the concept of optimal LAI to stands of rice grown under free air CO 2 enrichment (FACE). In this experiment, LAI increased with increasing nitrogen availability but was not affected by elevated CO 2 .…”
Section: Canopymentioning
confidence: 99%
“…However, the increase in LAI by elevated CO 2 was only 6-8%, both in the experiment and the prediction, suggesting that nitrogen availability is the most important factor for leaf development even under elevated CO 2 . Anten et al (2004) further analysed the canopy photosynthetic rates in the rice stands. There are clear indications that the positive effect of elevated CO 2 on canopy carbon gain increases with nitrogen availability (Fig.…”
Section: Canopymentioning
confidence: 99%
See 2 more Smart Citations
“…Oikawa et al (2013) reported that elevated CO 2 did stimulate the LAI in the soybeans cultivars but the LAI was also being regulated by the leaf production rate and leaf loss. The effects of (CO 2 ) on LAI are probably modified by N availability, which strongly controls leaf area growth (Anten et al 2003). The LAI of plants in elevated CO 2 might be affected by the insufficiency of N uptake.…”
Section: Effects Of Elevated Co 2 On Biomassmentioning
confidence: 99%